Effectiveness of Campus Gate Closure Policy During Zuhur Prayer in Shaping Students’ Religious Behavior at Muhammadiyah Purwokerto University - Abdullah, Husain; Amalia, Zahra Ayu; Febrianti, Nadia (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem: Universities not only function as centers of scientific development but also as spaces for character and religious value formation. At Muhammadiyah Purwokerto University (UMP), this is reflected in the policy of closing campus gates during zuhur prayer to encourage timely worship and support the internalization of Islamic values. Purpose: The policy is driven by the need to foster student religiosity through a supportive environment, as it does not develop automatically. Institutional efforts like campus regulations can be effective if designed wisely and inclusively. Methods: This article uses qualitative research with a research approach model of in-depth interviews with relevant sources and direct observation in the campus environment, data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. Findings: The study revealed mixed student responses to the campus gate closure policy during zuhur prayer at UMP. While 62.5% supported it for encouraging timely worship, 41.1% found it ineffective due to issues like limited mosque capacity, differing religiosity levels, and schedule disruptions. The policy may boost short-term compliance but lacks impact on long-term religious internalization without a more persuasive, student-centered approach. Research Implications: Proving that the campus policy in the form of closing the gate during zuhur prayer gets pros and cons from the campus community. The application of education with coercion methods is not relevant for students considering the needs and differences of students. Originality: The lack of students who are willing to fill out the questionnaire, henceforth it is prioritized to conduct more direct interviews.